AzuR From the SmtB/ArsR Family of Transcriptional Repressors Regulates Metallothionein in Anabaena sp. Strain PCC 7120 - Divya, T. V.; Acharya, Celin (Frontiers in Microbiology, 2022)
Metallothioneins (MTs) are cysteine rich, metal sequestering cytosolic proteins which play a key role in maintaining metal homeostasis and detoxification. We had previously characterized NmtA, a metallothionein from heterocystous, nitrogen fixing cyanobacterium Anabaena sp. strain PCC 7120 and demonstrated its role in providing protection against cadmium toxicity. In this study, we illustrate the regulation of Anabaena NmtA by AzuR (Alr0831) belonging to SmtB/ArsR family of transcriptional repressors. There is no experimental evidence for any functional role of AzuR as yet. It is observed that azuR is located within znuABC operon but in the opposite orientation and remotely away from nmtA locus. Sequence analysis of AzuR revealed a high degree of sequence identity with Synechococcus SmtB and distinct α5 metal binding site similar to that of SmtB. In order to characterize AzuR, we overexpressed it in E. coli and purified by chitin affinity chromatography. Far-UV circular dichroism spectroscopy indicated that the recombinant AzuR protein possessed properly folded structure. Glutaraldehyde cross-linking and size exclusion chromatography revealed that AzuR exists as a dimer of ~ 28 kDa in solution. Analysis of putative promoter region (100 bp upstream of nmtA ORF) identified the presence of 12-2-12 imperfect inverted repeat as the cis-acting element important for repressor binding. Electrophoretic mobility shift assays showed concentration dependent binding of recombinant dimeric AzuR with the promoter indicating that NmtA is indeed a regulatory target of AzuR. Binding of AzuR to DNA was disrupted in the presence of metal ions like Zn2+, Cd2+, Cu2+, Co2+, Ni2+, Pb2+ and Mn2+. The metal dependent dissociation of protein-DNA complexes suggested the negative regulation of metal inducible nmtA expression by AzuR. Overexpression of azuR in its native strain Anabaena 7120 enhanced the susceptibility to cadmium stress significantly. Overall, we propose negative regulation of Anabaena metallothionein by an α5 SmtB/ArsR metalloregulator AzuR.